Pregnancy and delivery in a patient with aortic prosthesis for Leriche syndrome - Sass, Nelson (2003)
CONTEXT: Leriche syndrome is a thrombotic obliteration of the bifurcation of the aorta, a rare condition that usually affects older men as a result of atherosclerosis. Women of childbearing age rarely need a vascular prosthesis (as a result of Leriche syndrome or other conditions) and there is no literature on an association between Leriche syndrome/vascular prosthesis and pregnancy/labor/delivery. CASE REPORT: A case of pregnancy and delivery in a 38-year-old patient with Leriche syndrome and an aortoiliac prosthesis is presented. The patient had no complications during pregnancy, and was admitted to the maternity hospital when close to term, to begin heparin therapy. Labor ensued spontaneously and a normal vaginal delivery occurred, resulting in a healthy infant. The authors present their considerations regarding the delivery route and the rationale for deciding in favor of vaginal childbirth.